<span>This one is the correct answer----->Multiply the bottom equation by 2 thus eliminating the y variable when the equations are added together.
</span><span>X + 6y = 2 ....top
</span><span>4x - 3y = 10...bottom
if we multiply the bottom equation by 2 .......... => 8x - 6y = 20
if we add it to the top one..........>(8+1)x +(6-6)y = (20+2)
then we solve for x => x = 22/9
then with the top equation, we solve for y == > y = -2/27</span>
Answer:
$24
Step-by-step explanation:
2/5 — dress
3/5 — remainder
1/2 of remainder = 1/2 × 3/5 = 3/10 — doll
rewrite fraction spent on dress: 4/10
dress - doll = $8
4/10 - 3/10 = 1/10
1/10 = $8
fraction of money left = 10/10 - 4/10 - 3/10
= 3/10
amount of money left = $8 × 3
$24
Answer:
28
Step-by-step explanation:
7+21=28
a-7=21
Multi-step equations are equations that require more than one step to solve.
For example:
2x+6 = 10 You subtract 6 from both sides
2x= 4 Divide both sides by 2
x=2 It took 2 steps to solve for x, so it is a muti-step equation.
One step equation:
2x =6 divide 2 by both sides
x=3 It only took one step, so it is an one-step equation.
Hope this can help you! Please put branliest answer if you like it!